The Influence Factors of School Management in Developing Entrepreneurship Literacy in Vocational Education - Zakso, Amrazi; Agung, Iskandar; Sulistiono, Agus Amin (World Journal of Vocational Education and Training, 2020)
This paper aims to explain the effect of school management on entrepreneurship and literacy education in vocational secondary education students (Indonesian: SMK). However, school management itself is estimated to be influenced by various factors which are also described in this paper, including: competence of school principals, curriculum development, entrepreneurship training, community participation, and local potential. The research sample was conducted at 14 vocational schools in 7 (seven) provinces in Indonesia, with a sample size of 824 students. Data collection was carried out through questionnaires, interviews, and FGD. In particular, questionnaires were distributed to students who had previously been tested to determine the validity and reliability of the existing questions, using Person and Cronbach Alpha criteria. The research analysis used Structural Equation Modeling (SEM) with the help of the Lisrel 8.70 program. The results showed that school management in entrepreneurship education was influenced by factors or variables of school principal competence, entrepreneurship curriculum, entrepreneurship training, community participation, and local potential. Furthermore, school management influences the management of teacher competence, learning facilities, and the application of entrepreneurship education in developing student entrepreneurial literacy. It is suggested that entrepreneurship education be an element in the vision, commitment and seriousness of school management. On the other hand, it is necessary to pay attention to the indicators that contribute the strongest value to each of the factors or variables that affect school management, and variables that are influenced by school management.